No functional beta 3-adrenergic receptors expressed in rat skeletal muscle cells - Gao Ben-Bo; Han Qi-De (Acta Pharmacologica Sinica, 2016)
AIM: To determine the functional role of beta 3-adrenoceptors (beta 3-AR) in rat skeletal muscle cells. METHODS: Nonselective beta-AR agonist isoprenaline (isoproterenol, Iso), beta 3-AR agonist CGP12177A which is a beta 1-/beta 2-AR antagonist and selective beta 3-AR antagonist SR59230A on cAMP accumulation was studied in primary cultured rat skeletal muscle cells. RESULTS: Iso stimulated cAMP accumulation in a concentration-dependent manner with EC50 of 1.51 nmol.L-1 and propranolol inhibited cAMP accumulation stimulated by Iso with KB of 3.47 nmol.L-1. CGP12177A had no effect on cAMP accumulation but inhibited cAMP production induced by Iso. SR59230A 10 nmol.L-1 did not inhibit cAMP production induced by Iso. CONCLUSION: The functional beta 3-AR are not present or at least not coupled to adenylyl cyclase activity in skeletal muscle cells.